A national multicenter study on 1072 DCIS patients treated with breast-conserving surgery and whole breast radiotherapy (COBCG-01 study). (February 2019) - Meattini, Icro; Pasinetti, Nadia; Meduri, Bruno; De Rose, Fiorenza; De Santis, Maria Carmen; Franco, Pierfrancesco; Lancellotta, Valentina; Rossi, Francesca; Saieva, Calogero; Desideri, Isacco; Delli Paoli, Camilla; D'Angelo, Elisa; et al.
Abstract: Background and purpose: Breast-conserving surgery (BCS) and whole breast radiation (RT) with or without endocrine therapy (ET) represent the standard of care for ductal carcinoma in situ (DCIS). The use of adjuvant treatments after surgery is still controversial in this setting. We performed a retrospective multicenter analysis on a series of DCIS patients treated with BCS and adjuvant RT. Materials and methods: We collected clinical data from nine Italian centers on 1072 women having a diagnosis of DCIS and treated between 1997 and 2012. We reported on the 5- and 10-year local recurrence (LR) rates, overall survival, and breast cancer specific survival (BCSS) employing the Kaplan–Meier method. Results: At a median follow-up of 8.4 years, 67 LR (6.3%) and 47 deaths (4.4%) were observed. LR rates at 5 and 10 years were 3.4% and 7.6%, respectively. BCSS rates at 5 and 10 years were 99.7% and 99.1%, respectively. At univariate regression analysis, postmenopausal state ( p  = 0.009), estrogen receptor (ER) ( p  = 0.0001) and progesterone receptor ( p  = 0.018) positivity and ET ( p  = 0.006) were inversely correlated with LR. Final surgical margins (FSM) status <1 mm was significantly correlated with higher LR ( p  = 0.003). At multivariate regression analysis postmenopausal state ( p  = 0.03), and ER positive ( p  = 0.045) maintained the significant favorable feature, while FSM <1 mm ( p  = 0.024) confirmed its negative impact on LR. Conclusions: Our real-life study pointed out the significant favorable prognostic role of postmenopausal state and ER positive status on LR occurrence. FSM <1 mm was significantly correlated to a higher chance to experience LR.